Benchmarking promoters of Fe/activated carbon catalyst for stable hydrogenation of CO2 to liquid hydrocarbons - Chen, Jingyu; Han, Seung Ju; Park, Hae Gu; Nasriddinov, Khasan; Zhang, Chundong; Jun, Ki Won; Kim, Seok Ki (Applied Catalysis B: Environmental, 2023)
Although iron-based catalysts are effective for long-chain hydrocarbon formation during the hydrogenation of CO2, they easily undergo deactivation. Thus, the deactivation behaviors of Fe-based catalysts supported on active carbon were investigated using various promoters. Ten metals were selected as promoters, and the resulting catalytic activities and selectivities over the course of 100 h were evaluated. Catalyst deactivation was primarily caused by changes of active phase and active crystallite size, namely active site transitions. Although the oxidation of Fe carbide is an unavoidable process, this can be alleviated by increasing the crystallite size to expose greater numbers of active sites and compensate for the deactivation process. The Cu-modified catalyst exhibited the highest CO2 conversion and C5+ yield, but was easily deactivated. In contrast, the Zn-modified catalyst exhibited stable activity, good C5+ yield, and high olefin/paraffin ratio by inhibiting oxidation and exhibiting a large increase in the active crystallite.
Keywords: Activated carbon catalysts; Active site; Active site transition; CO2 hydrogenation; Deactivation behavior; Fe/activated carbons; Iron-based catalyst; Liquid hydrocarbons; Modified catalysts; Promoter; Active site transitions; CO2 hydrogenation; Deactivation behavior; Iron-based catalyst; Promoter